Effect on the linearity improvement of TWTA by combining RF predistortion linearizer and digital predistortion algorithm - Xin HU; Gang WNAG; Zi-cheng WANG; Ji-run LUO (Tongxin xuebao, 2012)
In order to keep the adaptive digital predistortion algorithms valid,usually the output power level of the TWTA must be reduced,which corresponded a reduced efficiency of the TWTA.A predistortion technique was proposed by combining RF predistortion linearizer with adaptive digital predistortion algorithm.The gain and phase change of the TWTA with a RF predistortion linearizer circuit from small-signal input drive to saturated input drive were improved,respectively.Then the adaptive digital predistortion algorithm was used for the TWTA with the RF predistortion linearizer.The good linearity improvement can be reached with the less reduction for the output power level with this method.